The Influence of Work Environment and Workload on Turnover Intention with Job Satisfaction as an Intervening Variable in IZI - Tegar Irsyadi, Muhammad; Masydzulhak Djamil (Dinasti Publisher, 2023)
This study has the objective of strengthening the testing of the work environment and workload on the separation of employees between workplaces, which in this context is referred to as turnover intention. This study uses job satisfaction as an intervention variable. The method used to analyze the data is Smart PLS, using a saturated sample that includes the entire population, namely 82 employees. The results of the statistical processing found that all the variables tested had a significant positive effect. First, work can be influenced by work environment satisfaction. Second, work can also be affected by the burden of job satisfaction. Furthermore, the work environment is proven to affect turnover intention, as well as workload which also has an impact on turnover intention. In addition, turnover intention is also influenced by job satisfaction. All of these effects occur using job satisfaction as the intervening variable.